The Use of Project-Based Learning (PjBL) in Teaching English Speaking Skill - Anggraini, Risa; Zaharani, Hetty; Lumbangaol, Reni Rosianna (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
One of key features in Kurikulum Merdeka is the Project-Based Learning (PjBL) approach, which integrates technology into the classroom and focuses to prepare students’ readiness for encountering real-life challenges. In project-based learning, students design, execute, and assess projects that apply to real-world implementation in outside of the classroom. The participants of this research are tenth grade students of science class at SMAS Pelita Bulu Cina. The purpose of this research is to find out the impact of using project-based learning on students’ English speaking skills. Researchers used quantitative research focusing on pre-experimental research method design. To collect the data, researchers used test as the research instrument. There were pre-test and post test. Researchers analyzed the data by using inferential statistics and descriptive statistics. T-test formula was also used to get the speaking pretest and post test. The finding showed that the mean of pretest score was 71.40 and the post test was 84.25. The hypothesis test result indicated that t-table value for the post test score was 2.012, and significance value was less than ρ value (2- tailed) < 0.05, that was (0.001 < 0.05). It can be concluded that Ha was accepted and Ho was rejected. In short, project-based learning gave an impact on students’ speaking skill.